'Marea' on Lake Mareotis: A Roman Amphorae Dump, a Byzantine Period House, and Its Early Islamic Dwellers. Issue 2 (December 2019) - Gwiazda, Mariusz; Wielgosz-Rondolino, Dagmara
'Marea' is situated on the south-western shore of Lake Mareotis, some 40 km south-west of Alexandria and 4 km south of the Mediterranean coast, in a region that enjoyed considerable economic significance in the Graeco-Roman Period due to wine production. In 2011, a Polish expedition from the Archaeological Museum of Kraków, on behalf of the Polish Centre of Mediterranean Archaeology, initiated excavations at House H1 and focused their research in the structure's southern reaches. Then, in both 2014 and 2016, the excavations continued under the direction of a Polish team from the University of Warsaw. Based on this archaeological research as well as a stratigraphic analysis, it was possible to conclude that over the years the character of House H1 underwent substantial changes attested to by various kinds of alterations (wall demolition, introducing new partition structures and installations inside of rooms, constant rise of occupation levels). Our research enabled us to distinguish four main phases of habitation in this part of the archaeological site, beginning from the second century until its demise before the ninth century.